Soundscapes of Urban Parks in Cities with Populations of Over 100,000 in the Silesian Voivodeship - MITERSKA, Magdalena; KOMPAŁA, Janusz (Archives of Acoustics, 2021)
The article presents the results of soundscape assessments conducted in urban parks in the Silesian Voivodeship. The Silesian Voivodeship is characterised by a high degree of industrialisation and the greatest population density in Poland. The studies were conducted in the urban parks of all the cities in the voivodeship with populations of over 100,000 citizens. This selection was determined based on acoustic maps that are prepared for cities with populations of over 100,000 citizens as required by law, and on the fact that the role of urban parks is frequently marginalised in the context of city life. The goal of the studies was to define an objective acoustic appeal assessment method for urban parks in city centres. Measurements were carried out in 34 parks located in the centres of 12 cities. A-weighted sound levels LAeq were determined for 107 measuring points in urban parks and the streets adjacent to them. Differences in the A-weighted sound levels LAeq were presented for each studied park and the adjacent streets. Minimum and maximum sound values were subsequently determined for each measuring point. Significant differences in the minimum and maximum sound values in given locations were found despite minor differences in LAeq values. It was also discovered that though parks may often exhibit high A-weighted sound levels LAeq, there are other factors that influence the appeal of park soundscapes.